Bob Baxt address at the National Press Club on 16 March 1989 - Baxt, R. (Robert), 1938-; National Press Club (Australia) (1989)
Professor Bob Baxt, Chairman of the Trade Practices Commission, spoke about the Trade Practices Commission; the Trade Practices Act, its, uses, benefits and coverage; prevention of real competition in industry; litigation proceedings undertaken by the Commission; the Commission's involvement in the transition to deregulation; industry concentration and misuse of market power.
Copies available on cassette.
Photographs available.
Also available online
Keywords: Australia. -- Trade Practices Commission; Australia